OEM-supplier relations in the global auto and components industry: is there a business revolution?. (6th June 2005) - Sutherland, Dylan
This article describes some of the recent and profound changes witnessed in OEM-supplier relations in the auto industry. It considers different perspectives on the reasons for such change. A key question in analysis of the evolving supplier-OEM nexus relates to whether any inherent business logic underlies such change. This article argues that evidence increasingly suggests there is.